Bandgap calculation in Si quantum dot arrays using a genetic algorithm - Gómez-Campos, F.M.; Rodríguez-Bolívar, S.; de Jong van Coevorden, C.M.; Luque-Rodríguez, A.; Lara-Bullejos, P.; Carceller, J.E. (Physica. E, Low-dimensional systems & nanostructures, 2009)
In this work we present a fast and accurate genetic algorithm to determine the envelope functions and eigenenergies of the ground states of electrons and holes in low-dimensional complex semiconductor structures. We have developed the theoretical formalism of the algorithm in a general way in order to make it easy to include arbitrary nonparabolic and anisotropic band profiles in the calculations. From these results, calculation of the bandgaps of nanostructures can be carried out efficiently. Besides presenting and testing the algorithm, we calculate the ground state of electron and holes in two-dimensional quantum dot arrays, taking nonparabolicity and anisotropy into account.